Makna Kebahagiaan dalam Lafadz al-Farah menurut Tafsir al-Maraghi - Zulfassholihah, Farhana; Amrulloh, Muhammad; Faridah, Faridah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
Happiness is a theme that people always talk about. What is its essence and what paths should be taken to get it. But not every human being can find an easy and correct path to achieve his or her goals of happiness. The word that means happiness in the Qur'an is mentioned using several words, faroha or al-farah as one of the words that means happiness is found in 22 verses with various derivations. To facilitate understanding of the lafadz, this research will focus on the meaning of happiness on the lafadz al-farah according to the interpretation of al-Maraghi. This study uses the method of literature or library research with descriptive analytical approach or thematic studies. The results of research and discussion obtained are that the meaning of happiness in lafadz al-farah is generally divided into two; happiness that is positive and happiness that is negative. Positive happiness, such as happiness that comes from the grace of Allah, is happiness that brings gratitude and joy. While negative happiness such as worldly happiness and happiness that makes us arrogant and proud of ourselves is happiness that is ephemeral, temporary and not infrequently also becomes a sin. Some of the meanings of happiness that the author gets from the verses with the word al-farah are; Happiness for disobeying Allah's commands, happiness in disobedience, happiness that causes pride and pride, happiness over the blessings of the world, happiness for the grace of Allah, and happiness over the suffering of others.